Developing tests of impaired coordination for Paralympic classification: normative values and test–retest reliability. Issue 3 (September 2016) - Connick, Mark; Beckman, Emma; Deuble, Rebecca; Tweedy, Sean
Abstract Current methods of assessing coordination in Paralympic classification are non-instrumented and are based on ordinal scales of measurement and therefore impede the development of evidence-based methods of classification. This paper describes an instrumented battery of tests that measure impaired coordination in a way that will permit evidence-based classification. Test–retest reliability and normative values for each of the tests are reported. Twenty participants visited the laboratory on two occasions, each time completing 11 tests: three running-specific, lower-limb reciprocal tapping tests (yielding five outcome measures); four throwing-specific, upper-limb discrete tapping tests (yielding four outcome measures); and four wheelchair-specific, upper-limb reciprocal tapping tests yielding seven outcome measures. Reliability was evaluated using Intra-class Correlation Coefficients (ICCs), Standard Error of Measurement, Limits of Agreement and Paired t-tests. ICCs for fourteen of the 16 outcome measures were excellent (ICC ≥ 0.80), although systematic bias was evident in two of these—a unilateral, running-specific lower-limb tests on the non-dominant side, and a unilateral wheelchair-specific upper limb test on the dominant side. ICCs for two tests—a bilateral wheelchair-specific upper limb test (0.74), and a unilateral wheelchair-specific upper limb test on the non-dominant side (0.54)—were good and fair respectively. Results indicate that 12 of the measures evaluated have measurement properties that will facilitate the development of evidence-based methods of Paralympic classification in athletics. Positional adjustment and increased familiarization may improve reliability in the other four. Studies evaluating reliability of this test battery in people with coordination impairments are warranted.